Leveraging Distributed ledger technology in Unified beneficiary registry system of Malawi: A Task-technology fit Theory perspective - Frank Makoza (ZBW - Leibniz Information Centre for Economics, 2025)
Social cash transfer plays a critical role is supporting vulnerable communities to overcome poverty and shocks in Malawi. Digital technologies are integrated in social cash transfer to improve operations and deliver value to citizens. This paper analysed the potential use of distributed ledger technology (DLT) in unified beneficiary registry (UBR) system for social cash transfer in Malawi. The study used concepts from Technology-Task fit theory to understand social cash transfer tasks and characteristics of UBR system using secondary data. The findings showed that DLT may enhance the functions of UBR in supporting data sharing in a decentralised manner, maintaining transparency and accountability in transactions, supporting electronic payments, improving security, and addressing issues of infrastructure. The study highlights the significance of training and compliance with legal and regulatory frameworks. The study contributes towards understanding of the use of DLT in social protection programs in the context of developing countries. The paper suggest recommendations for practitioners and areas of further research.
Keywords: 330; Distributed Ledger Technology; Blockchain; Unified Beneficiary Registry; Task-Technology fit Theory; Social Cash Transfer; Malawi